A gar-bitten vertebrate coprolite from the Neogene of the Atlantic Coastal Plain, USA, and a new ichnospecies of Machichnus Mikuláš et al., 2006. Issue 3 (2nd October 2022) - Lindholm, Adam; Godfrey, Stephen J.; Ward, Lauck W.; Collareta, Alberto
Abstract: Vertebrate-bitten coprolites are seemingly rare; nonetheless, within the past dozen years, a handful of these composite trace fossils have been found and described. Here, we describe a single crocodile coprolite from the Lower Miocene Calvert Formation in New Kent County, Virginia, USA, showing bite marks. The size and morphology of the coprolite is consistent with a crocodilian origin. Seven parallel, gently curving gouges, of biogenic origin, disrupt the surface of the coprolite. As it is a medium preserving bite marks, this coprolite qualifies as a morderolite. Furthermore, because of the presence of larger/deeper primary, and finer secondary gouges, which we interpreted as individual tooth marks, the identity of the vertebrate that bit the coprolite is most likely gar (Lepisosteidae). Because other comparable coprolites preserving similar sets of primary and secondary gouges are known, this unique trace fossil is given a new ichnotaxonomic name, Machichnus dimorphodon isp. nov. Many more much smaller markings, interpreted as feeding traces by smaller organisms (possibly invertebrates) also ornament the surface of the coprolite.